2023
DOI: 10.1136/svn-2022-002071
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics of intracranial plaque in patients with non-cardioembolic stroke and intracranial large vessel occlusion

Abstract: ObjectiveTo determine the characteristics of intracranial plaque proximal to large vessel occlusion (LVO) in stroke patients without major-risk cardioembolic source using 3.0 T high-resolution MRI (HR-MRI).MethodsWe retrospectively enrolled eligible patients from January 2015 to July 2021. The multidimensional parameters of plaque such as remodelling index (RI), plaque burden (PB), percentage lipid-rich necrotic core (%LRNC), presence of discontinuity of plaque surface (DPS), fibrous cap rupture, intraplaque h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 41 publications
0
3
0
Order By: Relevance
“…Several previous studies also demonstrated that culprit lesions had higher non-calcified plaque volume, large fibro-fatty (analyzing in coronary plaques only), and necrotic core volume ( 17 , 23 , 24 ). We found that the culprit plaque in coronary artery had larger FLPV and FPV than the non-event plaque, but the corresponding FLPR and FPR were not significantly different, so the difference in volume may be due to the culprit plaque having a larger volume.…”
Section: Discussionmentioning
confidence: 74%
“…Several previous studies also demonstrated that culprit lesions had higher non-calcified plaque volume, large fibro-fatty (analyzing in coronary plaques only), and necrotic core volume ( 17 , 23 , 24 ). We found that the culprit plaque in coronary artery had larger FLPV and FPV than the non-event plaque, but the corresponding FLPR and FPR were not significantly different, so the difference in volume may be due to the culprit plaque having a larger volume.…”
Section: Discussionmentioning
confidence: 74%
“…Plaque hypo-intensity in ICAS serves as an imaging biomarker of intraplaque lipid core, and plaque contrast enhancement as intraplaque inflammation and neovascularization [19,20]. Both plaque imaging features provide potential clues to vulnerable plaques at high risk for rupture and future vascular ischemia [20,22,23]. We Values as medians (IQR) or numbers (%).…”
Section: Discussionmentioning
confidence: 99%
“…HR-VWI has gained prominence for its ability to characterize high-risk plaques and determine stroke etiology [23][24][25] , however, the role of remodeling in ICAS and its clinical implications remain poorly defined. The varied remodeling patterns evident in the pathological progression of de novo atherosclerosis raise questions about the determinants of remodeling's extent and direction.…”
Section: Introductionmentioning
confidence: 99%